Solid Organ Donation and Transplantation Activity in the Eurotransplant Area During the First Year of COVID-19. Issue 7 (11th April 2022) - Putzer, Gabriel; Gasteiger, Lukas; Mathis, Simon; van Enckevort, Arjan; Hell, Tobias; Resch, Thomas; Schneeberger, Stefan; Martini, Judith
Abstract : Background: Transplantation activity during the first wave of the coronavirus disease 2019 (COVID-19) pandemic was severely affected worldwide. This retrospective analysis aimed to assess the impact of COVID-19 on organ donations and transplantations in the Eurotransplant region during the first 12 mo of the pandemic. Specifically, we compared donor and transplantation numbers during both waves to determine whether transplant systems adapted to this new reality. Methods: All reported organ donations and transplantations from March 1, 2015, to February 28, 2021, were collected from the Eurotransplant International Foundation registry. The observation period from 2020 to 2021 was divided into three 4-mo periods, which were then compared with the corresponding periods of the preceding 5 y. COVID-19 cases for Eurotransplant countries were retrieved from the OurWorldInData.org database. Results: Overall, the number of organ donors decreased by 18.3% ( P  < 0.0001) and the number of organ transplantations by 12.5% ( P  > 0.0001) compared with previous years. Pancreas transplantation was the most affected, followed by kidney, liver, heart, and lung transplant. In detail, during period 1, the number of organ donors decreased by 26.2% ( P  < 0.0001) and the number of organ transplantations by 16.5% ( P  < 0.0001), in period 2 by 5.5% ( P  < 0.0091) and 4.9% ( P  < 0.0001), and in period 3 by 23.1% ( P  < 0.0001) and 16.4% ( P  < 0.0001), respectively. Conclusions: Organ donation and transplantation decreased drastically also during the second wave; however, despite the severity of the second wave, the decline was comparable with that of the first wave.